Experimental insights on iron-based alloys corrosion in water cooled loops - Martina Molinari; Eugenio Lo Piccolo; Raffaele Torella; Matteo D’Onorio; Nicholas Terranova; Gianfranco Caruso (Nuclear Materials and Energy)
This paper presents experimental findings on the behavior of iron-based alloys in environmental conditions typical of nuclear fusion technology, specifically focusing on material degradation, which is a critical aspect for the water cooling system of EU DEMO breeding blankets. The experimental campaign investigates potassium hydroxide’s role as an alkalizing agent, testing various concentrations to assess its impact on corrosion resistance. Additionally, it examines how oxygen levels affect localized corrosion development, which is crucial for mitigating corrosion risks in fusion applications. Seven 1000-hour tests were conducted to determine optimal conditions for corrosion reduction. Findings include identifying an oxygen concentration threshold to prevent piping cracking on EUROFER97 specimens.